Smart bookcase based on image recognition - Liu Ziyang (E3S Web of Conferences, 2021)
With the improvement of people’s living standards, the demand for books and the efficiency and accuracy of accessing books are also increasing. Because the information displayed to readers on the library management system is the position of the book when it is neatly arranged, sometimes the position of the book is inconsistent with the actual position of the book, which increases the difficulty for readers to find the target book. The traditional bookcase has a simple structure, and it takes a certain amount of time to search for books on weekdays. In view of the time-consuming situation of borrowing books, and in order to make it convenient for borrowers to find books, it is extremely important to develop a new type of networkable smart bookcase for libraries.